An Overview of Volume Rendering Techniques for Medical Imaging - S. Mady, Amr; Abou El-Seoud, Samir (International Journal of Online and Biomedical Engineering (iJOE), 2020)
One of the most valuable medical imaging visualizations or computer-aided diagnosis is Volume rendering (VR). This survey’s objective is reviewing and comparing between several methods and techniques of VR, for a better and more comprehensive reading and learning of both pros and cons of each method, and their use cases.